2014
DOI: 10.1186/1748-717x-9-70
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant boost IMRT-based neoadjuvant chemoradiotherapy for clinical stage II/III rectal adenocarcinoma: results of a phase II study

Abstract: AimThis study was designed to evaluate the efficacy and toxicities of concomitant boost intensity-modulated radiation therapy (IMRT) along with capecitabine and oxaliplatin, followed by a cycle of Xelox, in neoadjuvant course for locally advanced rectal cancer.Materials and methodsPatients with histologically confirmed, newly diagnosed, locally advanced rectal adenocarcinoma (cT3-T4 and/or cN+) located within 12 cm of the anal verge were included in this study. Patients received IMRT to the pelvis of 50 Gy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 26 publications
8
42
7
1
Order By: Relevance
“…34 The application of intensity-modulated radiation therapy (IMRT), while not yet standard treatment, may help to reduce this toxicity further without compromising response rates. 25,33,48–50 Similar to previous studies, we did not identify a lower likelihood of pCR in patients who received IMRT relative to standard external beam therapy.…”
Section: Discussionsupporting
confidence: 87%
“…34 The application of intensity-modulated radiation therapy (IMRT), while not yet standard treatment, may help to reduce this toxicity further without compromising response rates. 25,33,48–50 Similar to previous studies, we did not identify a lower likelihood of pCR in patients who received IMRT relative to standard external beam therapy.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, patients underwent radiotherapy in the supine position, which could reduce set-up uncertainty. Certain studies have suggested that the prone position for the treatment of rectal cancer patients had the advantage of small-bowel sparing [ 4 , 8 , 32 ]. However, Beriwal et al .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical target volume (CTV) was defined as the GTV plus areas considered at significant risk of harboring microscopic disease, including the mesorectum (perirectal fascia), presacral region, and internal iliac lymph node region. Based on our institution set-up data, the planning target volume (PTV) was generated by adding a 6-mm margin around the CTV in lateral and anterior-posterior directions, and an 8-mm margin in the superiorinferior direction [ 26 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%